Web-Based Graduation Plaque Information System Design Using UML and Waterfall Model: Perancangan Sistem Informasi Plakat Wisuda Berbasis Web Menggunakan UML dan Model Waterfall - Apriade Voutama; Elfina Novalia (Universitas Singaperbangsa Karawang, 2022)
The website-based graduation plaque information system is a forum for prospective graduation students to obtain information about graduation plaques. With the development of technology, it is necessary to have a system that is easily accessible, one of which is making a website-based system. The design utilizes a system design tool, namely UML (Unified Modeling Language) starting with determining the actors involved with the system using Use case diagrams, and using Activity diagrams to show actor activities and carrying out a more detailed flow using Sequence diagrams, and an overview of the bases. The data can be seen in the Class diagram. To clarify the appearance of the system design, a prototype of the interface design is needed as an illustration of the system model that is created. The research utilizes the computer science discipline, namely SDLC by applying the Waterfall model. Waterfall is a model that is used as a guide for research methods to focus on each sequence of stages. The system that has been built has received a good response from users so that this plaque information system can be used properly.